Եսայի Հասան-Ջալալյան Կաթողիկոսը որպես արցախահայ պետության գաղափարախոս ու կազմակերպիչ - Բալայան, Վահրամ (ԱրՊՀ հրատ․)
Освободительная борьба армянского народа в конце 17- го - начале 18-го века вступила в новую фазу. Появились идеологи этого движения, выступившие с определенными программами. В их ряду особенно заметную роль играл достойный представитель Арцахского рода Асан-Джалалянов, Есаи. С момента избрания католикосом (1703 г) он стал одним из преданных борцов освободительного движения и основателем новой государственности. The struggle for the independence of the Armenians in the late 17th and early 18th century entered a new phase. Some ideologists of this movement appeared, with their certain programs. Among them a particularly significant role was played by a worthy representative of the Artsakhian genus Hasan Jalalyan, Yesai. When elected as a Catholicos (1703), he became one of the faithful fighters of the liberation movement and the founder of the modern statehood.
Keywords: Հայ եկեղեցու պատմություն; Արցախ